2011
DOI: 10.1265/jjh.66.562
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Asbestos-Induced Carcinogenesis

Abstract: Several types of fibrous stone called asbestos have been an unexpected cause of human cancer in the history. This form of mineral is considered precious in that they are heat-, friction-, and acid-resistant, are obtained easily from mines, and can be modified to any form with many industrial merits. However, it became evident that the inspiration of asbestos causes a rare cancer called malignant mesothelioma. Because of the long incubation period, the peak year for malignant mesothelioma is expected to be 2025… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
110
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(114 citation statements)
references
References 30 publications
2
110
0
2
Order By: Relevance
“…Indeed, iron reduction can lower the risk for hepatic cancer (17) and probably in other cancers (18). Concerning mesothelioma, iron overload as a major pathogenic process has been recently studied (3,19,20). We reported that intraperitoneal injection of iron saccharate into rats induced mesothelioma (21) with loss of the Cdkn2a/2b tumor suppressor gene, the same genetic feature as asbestos-induced mesothelioma, supporting the hypothesis that iron overload is responsible for asbestos-induced mesothelial carcinogenesis (22).…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Indeed, iron reduction can lower the risk for hepatic cancer (17) and probably in other cancers (18). Concerning mesothelioma, iron overload as a major pathogenic process has been recently studied (3,19,20). We reported that intraperitoneal injection of iron saccharate into rats induced mesothelioma (21) with loss of the Cdkn2a/2b tumor suppressor gene, the same genetic feature as asbestos-induced mesothelioma, supporting the hypothesis that iron overload is responsible for asbestos-induced mesothelial carcinogenesis (22).…”
Section: Introductionsupporting
confidence: 60%
“…Although malignant mesothelioma is a relatively rare cancer originating from mesothelial cells on the somatic cavity, epidemiologic studies have firmly linked this tumor with asbestos exposure in the 1960s (1)(2)(3)(4). Asbestos is a group of natural fibrous minerals that reveal unique properties such as heat-, acid-, and friction-resistance with versatility and low cost for industrial use.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, three hypotheses exist regarding the pathogenesis of asbestos-induced mesothelioma. 4 The 'oxidative stress theory' 5 is based on the fact that fibrous mineral foreign substances in asbestos are phagocytosed by macrophages, which are unable to digest them, resulting in the massive generation of ROS. Alternatively, crocidolite and amosite may present catalyzing reactive environments with exposed surface iron.…”
mentioning
confidence: 99%
“…However, the roles and alterations of Th17 in silica-exposed patients are unknown and should be clarified through further research in order to obtain a better understanding of the immunological effects of silica on the human immune system. Many issues remain to be resolved, such as delineating the complications of SSc in SILs (Barnadas, 1986;Cowie, 1987Haustein, 1990Haustein & Anderegg, 1998;Sluis-Cremer, 1985), or those complications associated with malignant tumors such as mesothelioma and lung cancer in patients exposed to the mineral silicate asbestos (Greillier, 2008;Toyokuni, 2009;Miura, 2008). Regarding the relationship between tumor immunity and Treg function, it may be that Treg enhances cell numbers or function to reduce tumor immunity (Chattopadhyay, 2005;Danese & Rutella, 2007;Kretschmer, 2006).…”
Section: Silica-induced Dysfunction Of the Treg Fraction In Silsmentioning
confidence: 99%